KARAKTERISTIK KEMAMPUAN SISWA SMP KELAS VIII DALAM MENYELESAIKAN MASALAH PROBABILISTIK - Nur Qomaria (FKIP Universitas Islam Jember, 2016)
This study aimed to describe the ability of the 8th grade students in solving probabilistic problems. The probabilistic problems presented contain elements of uncertainty related to sample space, probability of an event, probability ratio, and conditional probability. The subjects of this study were the three groups of the 8th grade students with high, moderate and low mathematics skills. Data were collected through written test and interview. The results showed that low-ability student still think subjectively in responding to probabilistic problems. Meanwhile, moderate-ability student was at a transitional thinking stage between subjective and simple quantitative. High-ability student tended to think quantitative informally. Keywords: probabilistic problem, probability, 8th grade students